PENGARUH FAKTOR-FAKTOR PSIKOLOGIS TERHADAP KEPATUHAN PAJAK KENDARAAN BERMOTOR PEGAWAI PEMERINTAH DAERHA DI KABUPATEN TANA TORAJA - Kevin Afandi Willem; Elisabet Pali’; Olivia Devi Pongpeng (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the influence of attitude, subjective norms, perceived behavioral control, tax awareness and knowledge, and motivation on tax compliance. This research is motivated by the importance of improving taxpayer compliance as one of the key factors supporting the optimization of state revenue from the taxation sector. The study employed a quantitative research method, with data collected through questionnaires distributed to 55 respondents. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination with the assistance of statistical software. The results of the study indicate that, partially, the attitude variable has a positive and significant effect on tax compliance, with a t-value of 2.288 and a significance value of 0.026. Tax awareness and knowledge also have a positive and significant effect on tax compliance, with a t-value of 3.535 and a significance value of 0.001. Meanwhile, subjective norms, perceived behavioral control, and motivation do not have a significant effect on tax compliance. Simultaneously, attitude, subjective norms, perceived behavioral control, tax awareness and knowledge, and motivation significantly influence tax compliance, with an F-value of 13.564 and a significance value of 0.000. The coefficient of determination test shows an Adjusted R Square value of 0.538, indicating that 53.8% of the variation in tax compliance can be explained by the independent variables in this study, while the remaining 46.2% is explained by other factors outside the research model. Based on the findings, it can be concluded that attitude as well as tax awareness and knowledge are important factors in improving tax compliance, whereas subjective norms, perceived behavioral control, and motivation do not show a significant influence on tax compliance.